Analysis And Recommendations For The Vietnam’s Legal Framework On Cybercrime - Khoat, Nguyen Van (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Cybercrime is a global problem. There is no universal definition for cybercrime. Cybercrime is an ever-evolving phenomenon that challenges computer experts, states, law enforcement, and even researchers. Vietnam is one of the countries with the highest internet penetration worldwide. It is estimated that more than 80,000,000 people (80% of the population) are internet users and are at risk of cybercrime. Vietnam passed the Cybersecurity law in 2018. Also, Vietnam’s Criminal Code 2015 (amended 2017 addresses cybercrime. The article used a library-based secondary data analysis to compare cybercrime and cybercrime laws in Vietnam, Singapore, and the U.S. The article has established that cybercrime is widespread globally, and Vietnam is no exception. The article has also noted that Vietnam’s Cybersecurity Law 2018 should be amended to create a more balanced law that does not put most of its emphasis on the state. Also, Vietnam could learn from other countries like the U.S. about sharing information among cybercrime investigating agencies.